Development of a ROS Bridge Communication Framework for Real-Time Water Quality Monitoring in Aquaculture Floating Net Cages - Suprapto, Bhakti Yudho; Pratama, Ilham; Azim, Muhammad Rafian; Dwijayanti, Suci (International Journal of Electronics and Telecommunications, 2026)
Conventional floating net cages (KJA), widely used in aquaculture, generally lack integrated water quality sensors and real-time monitoring systems, resulting in inadequate water quality management and undetected causes of fish mortality. This study addresses this gap by equipping KJA with sensors that continuously monitor key water quality parameters, temperature, pH, and dissolved oxygen, and transmit data directly to a centralized server for real-time analysis and visualization via a web-based platform. To achieve fast and reliable wireless communication between the buoy and net cage, the TCP/IP protocol is implemented within the Robot Operating System (ROS) framework. This enables seamless interfacing of non-ROS devices, such as ESP32 microcontrollers, with the ROS system hosted on a laptop, facilitating rapid and stable data transfer. System performance tests under varying network conditions, server loads, and user access showed average data transmission delays of approximately 1 second, with maximum delays ranging from 4 to 9 seconds. Additional TCP/IP communication tests revealed an average packet delivery latency of just 11 milliseconds, demonstrating the high efficiency of the wireless link. User experience evaluation found that 90% of participants rated the web interface as both easy to use and informative, receiving an overall “excellent” usability score. These findings confirm that the developed system significantly improves the effectiveness of realtime water quality monitoring in KJA operations, potentially reducing fish mortality caused by water quality issues.